A Review Approach In Teaching Poetry To EFL Students : Adapting Generative Artificial Intelligence - Kumalasari, Cyintia; Marhamah, Marhamah; Wulandari, Fitri (JUPE : Jurnal Pendidikan Mandala, 2024)
Poetry is a dependable and successful teaching tool for the English language. It provides an incredible opportunity to practice speaking, writing, listening, and reading. Like other literary genres, poetry is meant to be admired and enjoyed. Developing this sense of appreciation and satisfaction in students who are not engaged in poetry is a challenging undertaking for any instructor. Poetry, as well as literature in general, was long removed from language education curricula because it was not useful for learning a foreign language in everyday life. Thankfully, there has been a resurgence of interest in the use of literature in language classrooms during the last few decades. Teaching by generative artificial intelligence is a method that helps teachers in the teaching process. Many people agree that generative artificial intelligence (AI) is one of the most significant technologies of the future, and it has caused a paradigm change in scientific study. There have been several studies about the use of generative AI. This paper focused on the challenges in teaching poetry and the approach of teaching poetry to EFL students by using generative AI